2001
DOI: 10.1002/ijc.1009
|View full text |Cite
|
Sign up to set email alerts
|

Role of P‐selectin in radiation‐induced intestinal inflammatory damage

Abstract: SUMMARY The aims of our study were to characterize the dose-and time-dependent changes in endothelial P-selectin expression and the role of this adhesion molecule as a mediator of radiation-induced inflammation. For that purpose, endothelial P-selectin expression was measured by the radiolabeled antibody technique in control and irradiated mice at 2, 6, and 24 hr following abdominal irradiation with 4 or 10 Gy; leukocyte endothelial cell interactions were assessed using intravital microscopy in intestinal venu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 30 publications
2
34
2
Order By: Relevance
“…Hallahan et al [16] showed in vitro that the lowest dose that induced translocation of P-selectin to the cell membrane was 2 Gy. Confirmatory evidence has been provided showing that P-selectin expression is significantly up-regulated in response to abdominal irradiation, and this regulation is dose-and time-dependent [6] . However, lack of P-selectin does not afford protection against radiationinduced inflammatory intestinal alterations probably because leukocyte adhesion is not solely a consequence of an increase in P-selectin mediated rolling; there is a release of proinflammatory mediators like PAF [5] or LTB4 [17] that may directly affect firm leukocyte adhesion.…”
Section: Molecular Determinants Of Leukocyte-endothelial Cell Adhesiomentioning
confidence: 78%
See 2 more Smart Citations
“…Hallahan et al [16] showed in vitro that the lowest dose that induced translocation of P-selectin to the cell membrane was 2 Gy. Confirmatory evidence has been provided showing that P-selectin expression is significantly up-regulated in response to abdominal irradiation, and this regulation is dose-and time-dependent [6] . However, lack of P-selectin does not afford protection against radiationinduced inflammatory intestinal alterations probably because leukocyte adhesion is not solely a consequence of an increase in P-selectin mediated rolling; there is a release of proinflammatory mediators like PAF [5] or LTB4 [17] that may directly affect firm leukocyte adhesion.…”
Section: Molecular Determinants Of Leukocyte-endothelial Cell Adhesiomentioning
confidence: 78%
“…Hallahan et al [19] showed that thoracic irradiation increases E-selectin expression in the pulmonary vascular endothelium of mice. In contrast, another study did not detect expression of this molecule in wild-type or in P-selectin deficient mice after abdominal irradiation at different doses (4, 10 Gy) and time (2 h or 24 h) points [6] . Recent studies have suggested that E-selectin could be involved in the antiinflammatory response after radiotherapy, mediating the drop in leukocyte adhesion after low dose irradiation (0.3-0.6 Gy) in vitro [20] .…”
Section: Molecular Determinants Of Leukocyte-endothelial Cell Adhesiomentioning
confidence: 84%
See 1 more Smart Citation
“…19,20 The cells were stained with APC-Cy7-conjugated anti-human CD45 antibody (Becton Dickinson) and human-CD45 þ cells were counted by flow cytometry analysis.…”
Section: Migration Assay Into Mouse Peripheral Organsmentioning
confidence: 99%
“…4) The survival rate increased in gene knockout mice lacking ICAM-1 or VCAM-1. 5) Remarkable progress has been made in recent years in designing new drugs targeting radiation-up-regulated adhesion molecules.…”
mentioning
confidence: 99%